2000
DOI: 10.1159/000016593
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility in the Assessment of Caries Lesion Behaviour: A Comparison between Conventional Film and Subtraction Radiography

Abstract: The purpose of this study was to compare reproducibility in the assessment of caries lesion behaviour in digital subtraction images and conventional radiographs. Ninety–seven pairs of conventional film bite–wings were included. The radiographs had been taken with a Kwik–Bite filmholder without further standardisation. The selection criterion was that at least one surface imaged in a bite–wing pair should show progresssion of a caries lesion from the first exposure to the second. The time interval between the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 30 publications
2
29
2
4
Order By: Relevance
“…9 Raters included in this study represented different professional experiences working in different institutions as well as different time lengths of expertise (long, intermediate and short time of experience). Yet, interrater agreement of 10 raters for caries lesion progression indicated substantial agreement (kappa 0.61), which is comparable with the results for 7 raters (kappa 0.70) in the study of caries lesion development by Wenzel et al 7 Pairwise interrater agreement varied, but substantial agreement was reached for many pairs of raters. The average intrarater agreement was 0.76, identical to that presented by Wenzel et al 7 for the assessment of caries lesion behaviour.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…9 Raters included in this study represented different professional experiences working in different institutions as well as different time lengths of expertise (long, intermediate and short time of experience). Yet, interrater agreement of 10 raters for caries lesion progression indicated substantial agreement (kappa 0.61), which is comparable with the results for 7 raters (kappa 0.70) in the study of caries lesion development by Wenzel et al 7 Pairwise interrater agreement varied, but substantial agreement was reached for many pairs of raters. The average intrarater agreement was 0.76, identical to that presented by Wenzel et al 7 for the assessment of caries lesion behaviour.…”
Section: Discussionsupporting
confidence: 81%
“…Yet, interrater agreement of 10 raters for caries lesion progression indicated substantial agreement (kappa 0.61), which is comparable with the results for 7 raters (kappa 0.70) in the study of caries lesion development by Wenzel et al 7 Pairwise interrater agreement varied, but substantial agreement was reached for many pairs of raters. The average intrarater agreement was 0.76, identical to that presented by Wenzel et al 7 for the assessment of caries lesion behaviour. Although difficult to compare, these results indicate higher interrater agreement than for caries detection by bitewing radiography reported in studies of high and medium quality.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The level of agreement among raters for radiographic assessment of caries lesion progression is however, largely unknown. Only one previous study was found regarding the agreement of caries lesions progression (Wenzel et al, 2000). Based on the reported variation among dentists in the detection and depth estimation of caries lesions, it can be expected that this variation may also exist for the assessment of caries lesion progression.…”
Section: Caries Lesion Progressionmentioning
confidence: 99%